FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENCEGAHAN PENYAKIT INFEKSI MENULAR SEKSUAL (IMS) PADA PEKERJA SOPIR ANGKUTAN UMUM JALUR “H” DIKOTA SORONG - Fikram Maswatu; S.L Momot; Jansen Parlaungan (Nursing Arts, 2018)
Sexually Transmitted Infections (STIs) are infectious or infectious diseases that are transmitted through sexual contact from the penis, vagina, anal and oral. Preliminary study at the City Health Office of Sorong, the number of data on cases of Sexually Transmitted Infections (STIs) in the last 2 years of 2016-2017 was 122 people consisting of 19 men and 103 women. Objective: To find out the factors related to the prevention of sexually transmitted infections (STIs) in public transport drivers in the "H" line in Sorong city. Research Method: This type of research is analytic observational using longitudinal cross sectional design. Statistical tests using chi-square consisted of 30 respondents. Independent variables are attitude and use of condoms. Results: Chi-square statistical test results on attitude relations showed p value 0.08> 0.05, which means that there was no relationship between respondents' attitudes towards condom use in taxi driver H. And the results of chi-square statistical tests on attitude relations showed p value = 0.05 by therefore p value 0.05 = 0.05, which means that there is a relationship between the attitude of respondents to condom use in street lane drivers H. Conclusion: There is no correlation between attitude with STI prevention measures on taxi drivers on the H line and there is a relationship between condom use and STI precautions on H. line taxi drivers.